A De Novo Mutation in MYH9 in a Child With Severe and Prolonged Macrothrombocytopenia. Issue 1 (January 2021) - Li, Kun; Jin, Runming; Xu, Wenfu; Shen, Yaqing; Lu, Ke; Wu, Xiaoyan
Abstract : Congenital macrothrombocytopenia is a diverse group of hereditary disorders caused by mutations in the MYH9 gene, which encodes the nonmuscle myosin heavy chain-A, an important motor protein in hemopoietic cells. Thus, the term MYH9 -related disease has been proposed, but the clinicopathologic basis of MYH9 mutations has been poorly investigated. Here, we report a sporadic case of Epstein syndrome, an MYH9 disorder, in a 4-year-old Chinese boy who presented with macrothrombocytopenia. He had no family history of thrombocytopenia, hearing loss, or renal failure. A de novo heterozygous MYH9 mutation, c.287C>T; p. (Ser96Leu), was found in this patient. Genotype-phenotype analysis of all reported mutations suggested a domain-specific relationship between the location of the MYH9 mutation and the penetrance of the nonhematologic characteristics of MYH9 -related disorders. Our study highlights the importance of suspecting MYH9 -related disease even in cases of chronic macrothrombocytopenia without a family history or extrahematologic symptoms.